Sistema produto - serviço como estratégia para o varejo de moda - Selau, Bruna Scaratti (Universidade do Vale do Rio dos Sinos, 2021)
The present study intends to do a comparison on the methodological processes used in strategic design and fashion and arises from the following research question: is it is possible to use the product-service system as a strategy in fashion retail? To answer this question, this research monograph intends, as a general objective, to develop a proposition for a fashion retail process using product system as strategy, and, as for the specific objectives, to: a) understand the fashion retail context; b) analyze the methodological fundaments of fashion design; c) comprehend the methodological fundaments of strategic design; d) identify and analyze a fashion retail brand for an application of the process developed in this research; e) understand the universe of the public that interacts with the brand; f) apply the developed process to the chosen brand, presenting a product-service fashion system as a result; g) validate the process and final result with the chosen company. As for the methodology used, this is a research of applied, exploratory nature, and of a quantitative approach. The approach method is inductive. As for the procedures, it is a bibliographic research and a case study. The techniques used for the data collection were bibliographic research, interviews, and focus group, which was used to validate the proposal for the process. Through the gathered information, it was possible to comprehend the methodological processes used in strategic design and fashion, as well as the necessities of fashion retail professionals, and, as a result, propose a development process for a product-service system for fashion retail and develop this product-service system based on the proposed process, and, additionally, validate it with a retail company.
Keywords: Desenvolvimento de coleção; Sistema produto-serviço; Processos metodológicos; Varejo de moda; Collection development; Product-service system; Methodological processes; Fashion retail